Bridging autoinflammatory and autoimmune diseases - Emad M. El-Shebiny; Enas S. Zahran; Sabry A. Shoeib; Eman S. Habib (SpringerOpen, 2021)
Abstract Background Autoimmunity is used to cause by impairment of adaptive immunity alone, whereas autoinflammatory was originally defined as a consequence of unregulated innate immunity. So, the pathogenetic mechanisms of autoimmune diseases were well-thought-out to be mediated by B and T lymphocytes. Whereas, autoinflammatory diseases were defined as unprovoked times of inflammation with the absence of a high titre of autoantibodies. Main body of the abstract Autoimmune and autoinflammatory diseases were split into two groups, but considering the similarities, it can be considered as only one group of diseases with a large immune pathological and clinical spectrum which involves at one end pure autoimmune diseases and the other pure autoinflammatory diseases. Conclusions We can safely conclude that there is bridging between autoinflammatory and autoimmune diseases.